Self-interest and the modernity of homo economicus. Issue 5 (8th May 2017) - Cojanu, Valentin
Abstract : Purpose: Criticism directed at neoclassical economics has failed to replace it with a similar grand theory. The authors argue that one possible explanation may lie in the failure of economists to formulate an opinion as to the philosophical foundations of the author's object of study. The paper aims to discuss this issue. Design/methodology/approach: The argument proceeds in two steps. First, the authors review the prevailing philosophical view of "the self-interest theory (S)", which is one of the most powerful constituents of today's economics, and social theorizing in general. Second, the authors present a reasoning framework in which rationality becomes intelligible within a schema of integrating the self's external and internal conditionalities into a unified view of human reasoning. Findings: Self-interest has been supposed to give the authors direction about what, concretely, to do, but, on the way, the authors have learned that defining rationality is necessarily a life-dependent process. The conflicts of reasons call for a revised S according to which rationality implies consistency among a person's competing behavioural drivers rooted in three ontological realms, natural, social, and cultural. Originality/value: First, understanding the purpose of one's actions in rational terms demands redirecting attention from outcomes in terms of utility, profits, or welfare to a social profile of a rational person, with real life coordinates in space and time, as well as the personal histories of that individual. A change in explaining aspirations leads, and this is the second implication, to change in defining the meaning of economic (or social) behaviour. Decision making is not necessarily a process of virtuously selecting the best available options, but assessing and acting according to the opportunity of choice; it is not about freedom of choice, but about the degree of freedom a person is willing and is able to take advantage of.